2022
DOI: 10.1097/hjh.0000000000003261
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for blood pressure reduction following isometric exercise training: a systematic review and meta-analysis

Abstract: Isometric exercise training (IET) is established as an effective antihypertensive intervention. Despite this, the physiological mechanisms driving blood pressure (BP) reductions following IET are not well understood. Therefore, we aimed to perform the first meta-analysis of the mechanistic changes measured following IET.Methods: PubMed, Cochrane library and SPORTDiscus were systematically searched for randomized controlled trials published between January 2000 and December 2021 reporting the effects of IET on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…This is an important consideration as the burden of hypertension and other cardiometabolic disease is larger in LMIC than in high income countries. 2 Based on our findings and other recent evidence, 10 , 17 the wall squat appears to therefore provide the best cost‐benefit in BP in hypertensives and is well tolerated, well adhered to and with no reports of adverse events in the present or previous wall squat interventions. Indeed, no dropouts and a 77% compliance with exercise sessions was reported in a recent year‐long‐wall squat intervention.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…This is an important consideration as the burden of hypertension and other cardiometabolic disease is larger in LMIC than in high income countries. 2 Based on our findings and other recent evidence, 10 , 17 the wall squat appears to therefore provide the best cost‐benefit in BP in hypertensives and is well tolerated, well adhered to and with no reports of adverse events in the present or previous wall squat interventions. Indeed, no dropouts and a 77% compliance with exercise sessions was reported in a recent year‐long‐wall squat intervention.…”
Section: Discussionsupporting
confidence: 66%
“…However, after phase 2, during which training frequency was reduced to 1 session per week, in the handgrip group SBP increased by .5 mmHg, while there was a further 1.8 mmHg decline in the wall squat group, representing a small magnitude but clinically relevant 3.8 mmHg greater SBP reduction in the wall squat group over the whole intervention–which aligns with the estimated >3 mmHg difference favoring wall squat over handgrip training in a recent meta‐analysis. 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This exercise should be performed at an intensity of 50% of maximum oxygen intake. Moreover, a meta-analysis has shown that resistance exercise also has antihypertensive effects [2]. A reduction in total peripheral resistance, potentially mediated by enhanced autonomic vasomotor control, is the primary cause of blood pressure (BP) reductions following isometric exercise.…”
mentioning
confidence: 99%